2018
DOI: 10.1038/s41591-018-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic hijacking of the stress response machinery in T cell acute lymphoblastic leukemia

Abstract: Cellular transformation is accompanied by extensive re-wiring of many biological processes leading to augmented levels of distinct types of cellular stress, including proteotoxic stress. Cancer cells critically depend on stress-relief pathways for their survival. However, the mechanisms underlying the transcriptional initiation and maintenance of the oncogenic stress response remain elusive. Here, we show that the expression of heat shock transcription factor 1 (HSF1) and the downstream mediators of the heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 80 publications
(112 reference statements)
8
80
1
Order By: Relevance
“…These data were consistent with a previous report that showed that Notch1 binds to the promoters of HSF1 to regulate the heat shock response pathway. 26 Moreover, further evidence revealed that the adoptive transfer of BMMs pretreated with lentivirus expressing HSF1 into Notch1 M-KO mice ameliorated IRinduced hepatocellular damage. Thus, HSF1 is crucial for Notch1 signaling-mediated immune regulation in response to IR stress.…”
Section: Discussionmentioning
confidence: 99%
“…These data were consistent with a previous report that showed that Notch1 binds to the promoters of HSF1 to regulate the heat shock response pathway. 26 Moreover, further evidence revealed that the adoptive transfer of BMMs pretreated with lentivirus expressing HSF1 into Notch1 M-KO mice ameliorated IRinduced hepatocellular damage. Thus, HSF1 is crucial for Notch1 signaling-mediated immune regulation in response to IR stress.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that HSF1 is abundant in the nuclei of mammary tumor cells in clinical biopsy samples, indicating constitutive activation of the heat shock response in cancer [38]. Perhaps most significantly, it has been shown that knockout of HSF1 in mouse tumor models, including p53-deficient or Her2-overexpressing spontaneous cancer, severely curtails tumor growth [13,[45][46][47][62][63][64]. These studies provide strong evidence for an important causal and essential role for the factor in tumorigenesis.…”
Section: Roles For Hsf1 In Cellular Processes Associated With Transfomentioning
confidence: 91%
“…These studies provide strong evidence for an important causal and essential role for the factor in tumorigenesis. In addition, higher levels of HSF1 mRNA found in tumor biopsies from a wide range of disease types may indicate a role for the expression of the factor in tumor morbidity ( Figure 2A,B) [47,65]. However, only in the case of hepatic cancer did we find a significant correlation between elevated HSF1 gene expression and the survival of patients ( Figure 2F) compared to breast and ovarian cancer, in which we could detect no significant relationship ( Figure 2D,E).…”
Section: Roles For Hsf1 In Cellular Processes Associated With Transfomentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression analyses were first performed with microarray data. For genome-wide detection, we then integrated polyA+ RNAseq analysis from public dataset GSE90715 (Kourtis et al, 2018) using T-ALL cell line treated with DMSO or GSI for the same time (24 hrs). Gene expression levels in duplicates normalized by fpkm were directly recovered in DMSO and GSI conditions.…”
Section: Statistical Analyses Of Gene Expression Datamentioning
confidence: 99%